N-terminal selective conjugation method widens the therapeutic window of antibody–drug conjugates by improving tolerability and stability - Min Ji Ko; Daehae Song; Juhee Kim; Jae Yong Kim; Jaehyun Eom; Byungje Sung; Yong-Gyu Son; Young Min Kim; Sang Hoon Lee; Weon-Kyoo You; Jinwon Jung (mAbs, 2021)
Antibody–drug conjugates (ADCs) are targeted therapeutic agents that treat cancers by selective delivery of highly potent cytotoxic drugs to tumor cells via cancer-specific antibodies. However, their clinical benefit is limited by off-target toxicity and narrow therapeutic windows. To overcome these limitations, we have applied reductive alkylation to develop a new type of ADC that has cytotoxic drugs conjugated to the N-terminal of an antibody through amine bonds introduced via reductive alkylation reactions (NTERM). To test whether the NTERM-conjugated ADCs can widen therapeutic windows, we synthesized three different ADCs by conjugating trastuzumab and monomethyl auristatin-F using three different methods, and compared their stability, efficacy, and toxicity. The NTERM-conjugated ADC was more stable in vitro and in vivo than the thiol-conjugated and the lysine-conjugated ADCs. The NTERM-conjugated ADC showed lower toxicity compared to other ADCs, whereas its efficacy was comparable to that of the thiol-conjugated ADC and better than that of the lysine-conjugated ADC. These results suggest that the NTERM conjugation method could widen the therapeutic window of ADCs by enhancing its stability and reducing toxicity.